2015
DOI: 10.1038/bonekey.2015.134
|View full text |Cite
|
Sign up to set email alerts
|

Role of Irisin on the bone–muscle functional unit

Abstract: Irisin was originally recognized as a hormone-like myokine secreted as a product of fibronectin type III domain containing 5 from skeletal muscle in response to exercise both in mice and humans. The first role attributed to Irisin was its ability to induce trans-differentiation of white adipose tissue into brown, but we recently demonstrated that Irisin also has a central role in the control of bone mass, even at lower concentration than required to induce the browning response. Considering how physical exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 51 publications
1
37
0
Order By: Relevance
“…Moreover, tibiae of mice treated with r-Irisin showed higher expression of osteopontin (OPN), one of the most abundant bone matrix proteins that is well known as mechanically responsive protein [17], as several studies showed that OPN expression was modulated in response to mechanical stimulation [18,19]. In accordance with the loading-mimetic function of Irisin, this myokine might be the mediator of the loading-induced increase of OPN expression [12].…”
Section: Irisin and The Bonementioning
confidence: 91%
See 2 more Smart Citations
“…Moreover, tibiae of mice treated with r-Irisin showed higher expression of osteopontin (OPN), one of the most abundant bone matrix proteins that is well known as mechanically responsive protein [17], as several studies showed that OPN expression was modulated in response to mechanical stimulation [18,19]. In accordance with the loading-mimetic function of Irisin, this myokine might be the mediator of the loading-induced increase of OPN expression [12].…”
Section: Irisin and The Bonementioning
confidence: 91%
“…Accordingly, Robling et al, showed that sclerostin expression was decreased by loading, resulting in increased bone formation, suggesting that it may be a key protein involved in mechanical loading [12,23]. Despite in vivo data indicating that r-Irisin, by downregulating sclerostin expression, participates in the signal-transduction pathway induced by mechanical loading, its direct effect on osteocyte is still unknown.…”
Section: Irisin and The Bonementioning
confidence: 93%
See 1 more Smart Citation
“…[8][9][10][11] The bioactive molecules involved in muscle-bone connection should be stressed due to the close relationship between skeletal muscle and bone. 12 Physical exercise, which is utilized as a nonpharmacological intervention in treatment protocols for some diseases, has been considered as being advantageous to metabolic and bone health. 13,14 Numerous studies have been designed to detect the molecules involved in the link between physical activity and bone acquisition and maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that different bone‐derived signals affect skeletal muscle; some of them, such as osteocalcin, insulin‐like growth factor 1 (IGF‐1), prostaglandin E2, and FGF‐23, display positive effects, while others, such as activin or TGF‐β, cause negative responses . Additionally, some muscle‐derived signals, such as interleukins (IL‐6, IL‐8, IL‐15), indirectly target bone through actions on other tissues, while other myokines, such as irisin, can affect bone directly …”
Section: Introductionmentioning
confidence: 99%